(untitled) (MSW Management Journal, 2026)
This study examines the impact of eco-labeling (EL) and eco-branding (EB) on purchase intention, with consumer perception (CP) acting as a mediating variable among consumers in Dhaka, Bangladesh. Utilizing the Theory of Planned Behavior (TPB), the study examines how environmental information and consumer perceptions impact sustainable purchasing intention. A quantitative, cross-sectional research design was employed, with data collected from 250 consumers via a structured questionnaire administered through Google Forms. Respondents were selected using a stratified sampling technique. Structural Equation Modeling (SEM) was utilized to analyze the hypothesized direct and mediating relationships among the study variables. The findings demonstrate that eco-labeling and eco-branding significantly influence consumer purchase intention. Mediation analysis reveals that consumer perception significantly mediates in the relationship between eco-labeling and purchase intention, while it is insignificant between eco-branding and purchase intention. Practically, the results indicate that organizations need to highlight authentic eco-labels and transparent environmental advantages to positively influence consumer attitudes and stimulate green purchasing behavior. The study focuses only on cross-sectional nature and a single location. The study suggests that future research should use long-term designs, cover more regions, and examine other factors such as environmental trust, green skepticism, and environmental knowledge.